Experimental data suggesting that inflammation mediated rat liver mitochondrial dysfunction results from secondary hypoxia rather than from direct effects of inflammatory mediators - Weidinger, Adelheid; Dungel, Peter; Perlinger, Martin; Singer, Katharina; Ghebes, Corina; Duvigneau, Catharina; Müllebner, Andrea; Schäfer, Ute; Redl, Heinz; Kozlov, Andrey V. (Frontiers in Physiology, 2013)
Systemic inflammatory response (SIR) comprises direct effects of inflammatory mediators (IM) and indirect effects, such as secondary circulatory failure which results in tissue hypoxia (HOX). These two key components, SIR and HOX, cause multiple organ failure (MOF). Since HOX and IM occur and interact simultaneously in vivo, it is difficult to clarify their individual pathological impact. To eliminate this interaction, precision cut liver slices (PCLS) were used in this study aiming to dissect the effects of HOX and IM on mitochondrial function, integrity of cellular membrane and the expression of genes associated with inflammation. HOX was induced by incubating PCLS or rat liver mitochondria at pO2<1% followed by reoxygenation (HOX/ROX model). Inflammatory injury was stimulated by incubating PCLS with IM (IM model). We found upregulation of inducible nitric oxide synthase (iNOS) expression only in the IM model, while heme oxygenase 1 (HO-1) expression was upregulated only in the HOX/ROX model. Elevated expression of interleukin 6 (IL-6) was found in both models reflecting converging pathways regulating the expression of this gene. Both models caused damage to hepatocytes resulting in the release of alanine aminotransferase (ALT). The leakage of aspartate aminotransferase (AST) was observed only during the hypoxic phase in the HOX/ROX model. The reoxygenation phase of HOX, but not IM, drastically impaired mitochondrial electron supply via complex I and II. Additional experiments performed with isolated mitochondria showed that free iron, released during HOX, is likely a key prerequisite of mitochondrial dysfunction induced during the reoxygenation phase. Our data suggests that mitochondrial dysfunction, previously observed in in vivo SIR-models is the result of secondary circulatory failure inducing HOX rather than the result of a direct interaction of IM with liver cells.